Spatial variation in carbon source use and trophic position of ringed seals across a latitudinal gradient of sea ice. (December 2022) - Carlyle, Cody G.; Roth, James D.; Yurkowski, David J.; Kohlbach, Doreen; Young, Brent G.; Brown, Thomas A.; Riget, Frank F.; Dietz, Rune; Ferguson, Steven H.
Graphical abstract: Highlights: Complementary biomarker analysis helps identify carbon source in ringed seal diets. Sea-ice derived carbon in ringed seal diets increases from low to high Arctic. Ringed seal trophic position increases from low to high Arctic. Ringed seals are a sentinel to quantify changes in ecosystem structure and function. Abstract: Anthropogenic climate change is causing changes to the Arctic sea-ice system with implications for the magnitude and timing of Arctic pelagic and ice-associated (sympagic) primary production that influences food web interactions. Ringed seals ( Pusa hispida ) are generalist predators that, as a species experience vastly different icescapes from low to high-Arctic latitudes. Quantifying spatial variation in their diet can help us understand how changes in sea-ice dynamics affect trophic interactions in Arctic marine food webs. However, multiple complementary analytical tools to examine variation in carbon source use and trophic dynamics in the diet of ringed seals have not yet been applied across their latitudinal range in the Arctic. We conducted stable isotope analysis (δ 13 C and δ 15 N) and measured highly branched isoprenoid diatom lipid biomarkers of ringed seals from the low, intermediate, and high Arctic (from 61.1°N to 77.5°N) to investigate spatial variation in their carbon source use and trophic position in relation to sea-ice dynamics. Both δ 13 C and highly branched isoprenoids indicated that ringed seals from higher latitudes had more sympagic carbon in their diet (liver δ 13 C: −18.3 ± 0.2 ‰, HBI: 89.9 ± 2.08 %) than ringed seals at lower latitudes (liver δ 13 C: −21.1 ± 0.1 ‰, HBI: 22.0 ± 2.73 %). Ringed seal trophic position increased from the low (3.78 ± 0.02) to high (4.76 ± 0.03) Arctic, suggesting increased fish consumption or a different trophic structure coinciding with the latitudinal change in carbon source. Ringed seals demonstrated a clear shift from low to high Arctic in the relative contribution of phytoplanktonic vs sympagic primary production. These patterns are likely linked to the vastly different icescapes in these environments and demonstrate that shifts in primary producer composition and Arctic food webs can be identified in ringed seal diets. Information on these prey and energy shifts over large spatial scales also provides insights into potential future changes to Arctic ecosystem function with continued sea-ice decline.